Existence/absence of the stx2e and f18 genes in Escherichia coli isolates from diarrhea-free pigs - Flores M., Alejandra (2024)
The aim of the study was to evaluate Escherichia coli isolates for the presence or absence of the f18 and stx2e genes. In total, 186 isolates obtained from piglets under 50 days of age that did not have diarrhoea at the time of sampling were studied. The animals were from four high-tech breeding farms located in the Lima region. Sampling was done in 2019 as part of a preliminary study using rectal swabs. A commercial purification kit was used for DNA extraction and a conventional PCR protocol was used for gene detection. No PCR product for stx2e or f18 could be detected in any of the E. coli isolated from these piglets.